2008
DOI: 10.1111/j.1467-2979.2008.00275.x
|View full text |Cite
|
Sign up to set email alerts
|

Historical distribution of right whales in the North Pacific

Abstract: Fisheries records provide some of the only information on pre‐fishing distribution and abundance for species that were depleted before the advent of modern scientific investigations. This paper interprets records of the early history of whaling for North Pacific right whales (Eubalaena pacifica). The current population occupies only a fraction of its historical range. Historical distributions of several whale species have been inferred from charts prepared by Matthew Fontaine Maury in the early 1850s and Charl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 11 publications
0
42
0
Order By: Relevance
“…Finally, I investigated how the predictions for the western subpopulation responded to the removal of potentially biasing records (i.e. right whale records from the northern Sea of Okhotsk likely represent bowhead whales [Josephson et al 2008b], while it is unclear whether the Sea of Japan represents a foraging ground, or simply a migratory corridor [Brownell et al 2001]). In total, I built 8 annual and 14 seasonal models by systematically modifying the temporal resolution and spatial extents of the data used.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, I investigated how the predictions for the western subpopulation responded to the removal of potentially biasing records (i.e. right whale records from the northern Sea of Okhotsk likely represent bowhead whales [Josephson et al 2008b], while it is unclear whether the Sea of Japan represents a foraging ground, or simply a migratory corridor [Brownell et al 2001]). In total, I built 8 annual and 14 seasonal models by systematically modifying the temporal resolution and spatial extents of the data used.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, the Pacific Decadal Oscillation, which has a strong influence on weather patterns in the North Pacific, was actually in a cooler phase from 1950 to 1976 than during the right whale whaling era (Biondi et al 2001). Finally, whaling occurred in the Bering Sea in summer throughout the 1840s (Josephson et al 2008b), and accounts from Arctic logbooks contain no indication of unusually cold conditions (Wood & Overland 2003). Thus, while an overall warming trend in air temperature is evident in the region (Moore et al 2002), there is little to suggest that the ocean climate in the North Pacific during the mid19th century was in any way dramatically different from the 20th century.…”
Section: Scaling Assumptions and Model Performancementioning
confidence: 99%
See 1 more Smart Citation
“…North Pacific right whales are among the most endangered whale species on earth, and there remain huge gaps in our knowledge of basic biological information about them, including the location of wintering grounds and population structure. Historic and recent observations support the division of North Pacific right whales into an eastern and a western stock , Clapham et al 2004, and a recent reexamination of data from whaling logbooks corroborates a bimodal distribution of right whales, with very few sightings in the central North Pacific (Josephson et al 2008). Omura (1958Omura ( , 1986 suggested that the western stock be further divided into 2 subpopulations, one migrating within the Sea of Japan and summering in the Sea of Okhotsk, and another migrating along the Pacific coasts of Japan and the Kamchatka peninsula, with some animals entering the Bering Sea by early summer.…”
Section: Implications For Right Whale Managementmentioning
confidence: 87%
“…Once common in many areas of the North Pacific and Bering Sea, the species was severely depleted by intensive whaling in the mid 19th century (Brownell et al 2001;Scarff 2001;Josephson et al 2008). Although numbers may have been increasing by the mid 20th century following international protection in 1935 (Brownell et al 2001), large illegal and unreported catches by Soviet whalers in the 1960s likely reversed any nascent recovery and the species remains endangered today (Ivashchenko and Clapham 2012).…”
Section: Introductionmentioning
confidence: 99%